Functional genomics of GPR126 in airway smooth muscle and bronchial epithelial cells. Issue 7 (24th June 2021) - Hall, Robert J.; O'Loughlin, Jonathan; Billington, Charlotte K.; Thakker, Dhruma; Hall, Ian P.; Sayers, Ian
Abstract: GPR126 is an adhesion G protein‐coupled receptor which lies on chromosome 6q24. Genetic variants in this region are reproducibly associated with lung function and COPD in genome wide association studies (GWAS). The aims of this study were to define the role of GPR126 in the human lung and in pulmonary disease and identify possible casual variants. Online tools (GTEx and LDlink) identified SNPs which may have effects on GPR126 function/ expression, including missense variant Ser123Gly and an intronic variant that shows eQTL effects on GPR126 expression. GPR126 signaling via cAMP‐mediated pathways was identified in human structural airway cells when activated with the tethered agonist, stachel. RNA‐seq was used to identify downstream genes/ pathways affected by stachel‐mediated GPR126 activation in human airway smooth muscle cells. We identified ~350 differentially expressed genes at 4 and 24 hours post stimulation with ~20% overlap. We identified that genes regulated by GPR126 activation include IL33, CTGF, and SERPINE1, which already have known roles in lung biology. Pathways altered by GPR126 included those involved in cell cycle progression and cell proliferation. Here, we suggest a role for GPR126 in airway remodeling.